Multifunctional corrosion-resistant flame-retardant thermal-insulation tpo co-extrusion composite film and preparation method thereof

CN122976152APending Publication Date: 2026-10-27DALIAN HENGTAI HENGBAO PLASTIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611209964.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有TPO材料多功能改性存在性能拮抗、多层共挤结构层间结合力弱、功能填料与基体相容性差且分散不均的不足,本发明的目的在于提供一种采用三层功能分区与界面过渡耦合设计的多功能耐腐蚀阻燃隔热TPO共挤复合膜,并提供所述复合膜的制备方法

Benefits of technology

1.本发明采用三层功能分区的结构设计,将耐腐蚀、阻燃、隔热三类功能分别配置于独立层位进行针对性优化,避免了多类功能填料在同一基体中共混引发的相容性差、性能相互抵消的问题;各层功能屏障相互配合形成多级协同防护体系,在同步提升多项核心性能的同时,有效保留了材料的力学性能与热风焊接施工性能,解决了传统单一基体改性难以兼顾多功能的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a multifunctional corrosion-resistant flame-retardant heat-insulating TPO co-extrusion composite film and a preparation method thereof, and belongs to the technical field of high polymer functional composite materials and multi-layer co-extrusion molding. The composite film is integrally formed in a three-layer co-extrusion structure, and sequentially comprises a corrosion-resistant functional layer, a transition bonding layer and a flame-retardant heat-insulating functional layer from top to bottom. The corrosion-resistant functional layer takes high-density weather-resistant TPO resin as a matrix, and is matched with sheet-shaped barrier fillers and fluorinated polymer micropowder to build a multi-stage corrosion-resistant barrier. The transition bonding layer adopts a maleic anhydride grafted polyolefin system, matches the interlayer melt performance and realizes firm combination of the interface. The flame-retardant heat-insulating functional layer takes elastomer modified TPO as a matrix, is compounded with aerogel-based composite flame retardant and hollow heat-insulating fillers, and cooperatively realizes the integration effect of flame retardation and heat insulation. Through the functional partition and interface coupling design, the application synchronously improves the corrosion resistance, flame retardation, heat insulation and mechanical welding performance, and can be widely applied to multi-working-condition scenes such as chemical corrosion protection, new energy power battery protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer functional composite materials technology, specifically relating to a multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film and its preparation method. Background Technology

[0002] Thermoplastic polyolefin (TPO) is a thermoplastic elastomer material formed by blending polypropylene, polyethylene and polyolefin elastomers. It combines the high elasticity of rubber with the hot processing properties of plastics. With its excellent weather resistance, chemical corrosion resistance, hot air welding construction and environmentally friendly recyclability, it has become one of the core substrates in the fields of building waterproofing and industrial corrosion protection.

[0003] As the complexity of downstream engineering scenarios increases, single-function TPO materials are no longer sufficient to meet the requirements of complex environments: chemical corrosion protection scenarios require materials to withstand acid, alkali, and salt corrosion as well as high-temperature environments; building-integrated photovoltaic (BIPV) roofing requires materials to have waterproof, flame-retardant, and heat-insulating energy-saving functions; and new energy power battery pack protection requires materials to have electrolyte corrosion resistance, flame retardancy, heat insulation, and electrical insulation properties. The market has created a rigid demand for TPO membrane materials that integrate multiple functions such as corrosion resistance, flame retardancy, and heat insulation.

[0004] In existing technologies, functional modification of TPO materials often focuses on optimizing a single performance, making it difficult to achieve synergistic improvement of multiple properties. Corrosion resistance modification often uses highly crystalline TPO resin combined with sheet-like barrier fillers to improve media resistance by extending the penetration path. However, the highly crystalline matrix has poor compatibility with polar flame retardants and thermal insulation fillers, and interface defects easily occur after blending, which reduces the integrity of the corrosion barrier. Flame retardant modification often uses high-filling amounts of metal hydroxides such as magnesium hydroxide and aluminum hydroxide, or intumescent flame retardants. To achieve the ideal flame retardant rating, the filler content usually exceeds 35%, which significantly degrades the material's elongation at break, low-temperature resistance, and weldability. Simultaneously, the introduction of a large amount of inorganic filler increases the material's thermal conductivity, thus weakening the thermal insulation effect. Thermal insulation modification often relies on high-reflective surface coatings or adhesive-coated aerogel layers. Surface reflective layers are prone to rapid attenuation of thermal insulation effect due to dust accumulation and aging; adhesive bonding processes suffer from poor interlayer adhesion, easy delamination and peeling after long-term use, and adhesives are prone to degradation and failure in corrosive media environments. Currently available multilayer TPO composite solutions generally lack specialized interlayer interface adaptation designs. The melt rheological properties and crystallization rates of different functional layers vary greatly. After co-extrusion molding, the interlayers are only bound by simple physical entanglement, resulting in low peel strength. After thermal aging or immersion in corrosive media, interlayer separation, bubbling, and other failure phenomena are prone to occur, making it impossible to achieve long-term stable synergy of multiple properties.

[0005] Therefore, developing a TPO co-extruded composite film that combines excellent corrosion resistance, flame retardancy, heat insulation properties, and long-term interfacial stability is a technical problem that the industry urgently needs to solve. Summary of the Invention

[0006] To address the shortcomings of existing multifunctional modified TPO materials, such as performance antagonism, weak interlayer bonding in multilayer co-extrusion structures, and poor compatibility and uneven dispersion of functional fillers with the matrix, the present invention aims to provide a multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film with a three-layer functional partition and interface transition coupling design, and to provide a method for preparing the composite film.

[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention provides a multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film and its preparation method.

[0008] The multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film of the present invention is a three-layer co-extruded integral molding structure, consisting of a corrosion-resistant functional layer, a transition adhesive layer, and a flame-retardant and heat-insulating functional layer from top to bottom, with the sum of the thicknesses of the three layers being 100%.

[0009] The corrosion-resistant functional layer uses high-density weather-resistant TPO resin as the matrix, and adds compounded sheet-like barrier filler and polyvinylidene fluoride micro powder. The tortuous path of the sheet-like filler and the low surface energy barrier of the fluorine micro powder jointly improve the resistance to media penetration. The compound sheet-like barrier filler is a mixture of ultrafine talc powder, mica powder and organically modified montmorillonite in a mass ratio of 2:1:1.

[0010] The transitional adhesive layer uses maleic anhydride-grafted polyolefin elastomer and maleic anhydride-grafted polypropylene as the matrix, with the addition of nano-silica and melamine cyanurate; by compounding two grafted resins with different grafting rates, the polarity difference between the upper and lower layers is matched, thereby improving the interlayer bonding strength; the grafting rate of the maleic anhydride-grafted polyolefin elastomer is 0.8% to 1.2%, and the grafting rate of the maleic anhydride-grafted polypropylene is 1.0% to 1.5%.

[0011] The flame-retardant and heat-insulating functional layer uses general-purpose TPO resin and POE elastomer as the matrix, and adds aerogel-based composite flame retardant and compounded hollow heat-insulating filler. The aerogel-based composite flame retardant is a composite of ammonium polyphosphate and diethylaluminum hypophosphite supported on ammonium silica aerogel, with a loading mass ratio of aerogel:ammonium polyphosphate:diethylaluminum hypophosphite = 1:3:2. The compounded hollow heat-insulating filler is a mixture of hollow glass microspheres and hollow ceramic microspheres with a mass ratio of 1:1. The aerogel carrier improves the dispersion efficiency of the flame retardant, and the hollow filler reduces the thermal conductivity of the system. The two work synergistically to achieve a simultaneous improvement in flame-retardant and heat-insulating performance.

[0012] Furthermore, the total thickness of the composite membrane is 1.2 to 2.0 mm, of which the thickness of the corrosion-resistant functional layer accounts for 30% to 40%, the thickness of the transition bonding layer accounts for 20% to 30%, and the thickness of the flame-retardant and heat-insulating functional layer accounts for 30% to 40%.

[0013] Further, by weight, the corrosion-resistant functional layer comprises the following components: 65 to 85 parts of high-density weather-resistant TPO resin, 10 to 30 parts of compounded sheet-like barrier filler, 1 to 5 parts of polyvinylidene fluoride micropowder, 0.5 to 2 parts of compounded antioxidant, 0.5 to 2 parts of hindered amine light stabilizer, and 0.3 to 1 part of processing aid; the polyvinylidene fluoride micropowder has a particle size of 5 to 10 μm, the compounded antioxidant is a compound system of hindered phenols and phosphites, and the processing aid is polyethylene wax or calcium stearate.

[0014] Further, by mass parts, the transition adhesive layer is composed of the following components: 60 to 80 parts of maleic anhydride-grafted polyolefin elastomer, 10 to 20 parts of maleic anhydride-grafted polypropylene, 2 to 8 parts of nano-silica, 0.2 to 1 part of silane coupling agent, and 1 to 5 parts of melamine cyanurate; wherein the silane coupling agent is KH-550.

[0015] Further, by weight, the flame-retardant and heat-insulating functional layer is composed of the following components: 50 to 70 parts of general-purpose TPO resin, 10 to 20 parts of POE elastomer, 15 to 30 parts of aerogel-based composite flame retardant, 5 to 15 parts of compounded hollow heat-insulating filler, 0.3 to 1.2 parts of silane coupling agent, and 0.5 to 1.5 parts of processing aid.

[0016] This invention also provides a method for preparing the above-mentioned multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film, which is prepared using a three-layer co-extrusion casting process, specifically including the following steps: (1) Preparation of aerogel-based composite flame retardant and preparation of functional masterbatch: First, the silica aerogel is aminated by silane coupling agent, and then ammonium polyphosphate and aluminum diethylphosphite are loaded by impregnation loading method. After drying, the aerogel-based composite flame retardant is obtained; the composite flame retardant and the compound hollow heat insulation filler are prepared into functional masterbatch. (2) Ingredients and mixing: According to the formula ratio of each layer, the matrix resin, functional masterbatch and remaining additives are put into the high-speed mixer and mixed evenly at room temperature, and then fed into the corresponding extruder hoppers respectively. (3) Three-layer co-extrusion molding: Three single-screw extruders are used to plasticize three layers of material respectively. The melt is stacked by the co-extrusion distributor and then extruded into a preform through a flat die. (4) Casting, cooling and shaping: The extruded composite film preform is introduced into a three-roll casting calender and is shaped by segmented gradient cooling; (5) Post-processing and winding: After cooling and shaping, the composite film is subjected to surface corona treatment and constant temperature aging to eliminate internal stress. Finally, it is cut to length, inspected and wound to obtain the finished product.

[0017] Further, the temperature parameters of each extruder in step (3) are set as follows: for the corrosion-resistant functional layer extruder, the feeding section is 180 to 190°C, the plasticizing section is 200 to 210°C, and the homogenizing section is 205 to 220°C; for the transition bonding layer extruder, the feeding section is 170 to 180°C, the plasticizing section is 190 to 200°C, and the homogenizing section is 195 to 210°C; for the flame-retardant and heat-insulating functional layer extruder, the feeding section is 175 to 185°C, the plasticizing section is 195 to 205°C, and the homogenizing section is 200 to 215°C; the temperature of the co-extrusion distributor and the die head is 205 to 215°C; and the overall melt extrusion rate is 8 to 15 m / min.

[0018] Furthermore, the temperature parameters of the three-roll casting calender in step (4) are set as follows: the temperature of the first roll is 80 to 90°C, the temperature of the second roll is 50 to 60°C, and the temperature of the third roll is 25 to 35°C.

[0019] Furthermore, in step (5), the corona treatment power is 8 to 12 kW, the constant temperature aging temperature is 40 to 50 °C, and the aging time is 24 h.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention adopts a three-layer functional partition structure design, which configures the three functions of corrosion resistance, flame retardancy and heat insulation in independent layers for targeted optimization, avoiding the problems of poor compatibility and mutual cancellation of performance caused by the co-mixing of multiple functional fillers in the same matrix; the functional barriers of each layer cooperate to form a multi-level synergistic protection system, which simultaneously improves multiple core performances while effectively preserving the mechanical properties and hot air welding performance of the material, and solves the technical bottleneck of traditional single matrix modification that is difficult to achieve multiple functions.

[0021] 2. This invention features a dedicated transition adhesive layer that utilizes the thermal diffusion entanglement of the molecular chains of polar grafted polyolefins and the interaction with polar groups to achieve a strong bond at the interface of the upper and lower functional layers. At the same time, the transition adhesive layer can effectively prevent the migration and precipitation of functional additives between layers. Under harsh conditions such as thermal aging and immersion in corrosive media, it can still maintain the integrity of the interlayer structure, avoiding the delamination, bubbling and other failure phenomena that are prone to occur in traditional multilayer composite structures, and significantly improving the performance stability of the product throughout its entire life cycle.

[0022] 3. This invention improves the interfacial compatibility between inorganic functional fillers and polyolefin matrices through surface modification and compound system design of functional fillers, and enhances the uniformity of filler dispersion in the matrix, achieving excellent functional effects at low filler levels. Combined with the matrix design of elastomer modification, it effectively maintains the flexibility and processing fluidity of the material, ensuring the stable performance of functional properties while avoiding defects such as material embrittlement and increased processing difficulty caused by high filler levels, thus ensuring the uniformity of product quality. Detailed Implementation

[0023] The present invention will be further described in detail below with reference to the embodiments. The embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.

[0024] Example 1 This embodiment corresponds to the upper limit of the formulation component range, focusing on enhancing corrosion resistance and flame retardant properties. The total thickness of the composite film is 1.8 mm, and the thickness ratio of each layer is 30% for the corrosion-resistant functional layer, 30% for the transition bonding layer, and 40% for the flame-retardant and heat-insulating functional layer.

[0025] Formulas for each layer (by weight parts) Corrosion-resistant functional layer: 65 parts of high-density weather-resistant TPO resin, 30 parts of compounded sheet barrier filler, 5 parts of polyvinylidene fluoride micro powder, 2 parts of compounded antioxidant, 2 parts of hindered amine light stabilizer, and 1 part of processing aid.

[0026] Transitional adhesive layer: 60 parts maleic anhydride-grafted polyolefin elastomer, 20 parts maleic anhydride-grafted polypropylene, 8 parts nano silica, 1 part silane coupling agent, and 5 parts melamine cyanurate.

[0027] Flame-retardant and heat-insulating functional layer: 50 parts of general-purpose TPO resin, 20 parts of POE elastomer, 30 parts of aerogel-based composite flame retardant, 15 parts of compounded hollow heat-insulating filler, 1.2 parts of silane coupling agent, and 1.5 parts of processing aid.

[0028] Preparation method (1) Functional filler pretreatment and masterbatch preparation: Aerogel-based composite flame retardant and compound hollow heat insulation filler are put into a high-speed mixer, heated to 80°C, and silane coupling agent of the corresponding proportion is added at a uniform speed. The surface modification is completed by high-speed stirring for 15 minutes and the material is discharged for later use. The modified filler is mixed with the corresponding matrix resin and some additives in proportion, and then melt-blended and granulated by a twin-screw extruder to prepare functional masterbatch for corrosion-resistant layer and flame-retardant heat insulation layer. The twin-screw extrusion temperature range is 180~210°C and the screw speed is 300r / min.

[0029] (2) Ingredients and mixing: Weigh the matrix resin, functional masterbatch and remaining additives according to the formula ratio of each layer, put them into the high-speed mixer and mix at room temperature for 12 minutes. After mixing evenly, send them into the corresponding extruder hopper.

[0030] (3) Three-layer co-extrusion molding: Three single-screw extruders are used to plasticize the three layers of material respectively. The melt is stacked by the co-extrusion distributor and then enters the flat die to extrude the preform. The extruder temperature for the corrosion-resistant functional layer is: feeding section 190℃, plasticizing section 210℃, homogenizing section 220℃; the extruder temperature for the transition bonding layer is: feeding section 180℃, plasticizing section 200℃, homogenizing section 210℃; the extruder temperature for the flame-retardant and heat-insulating functional layer is: feeding section 185℃, plasticizing section 205℃, homogenizing section 215℃; the temperature of the co-extrusion distributor and the die is 215℃; the overall extrusion rate of the melt is 8m / min, and the screw speed is matched to control the thickness of each layer to meet the design ratio.

[0031] (4) Casting, cooling and shaping: The extruded film preform is introduced into a three-roll casting calender for segmented gradient cooling and shaping. The temperature of the first roll is 90℃, the temperature of the second roll is 60℃, and the temperature of the third roll is 35℃. The total thickness is controlled to be 1.8mm by the gap between the rolls.

[0032] (5) Post-processing and winding: The cooled composite film is subjected to corona surface treatment with a processing power of 12kW; then it is sent to a 50℃ constant temperature aging chamber for 24h to eliminate internal stress, and finally the finished product is obtained after length cutting, appearance inspection and winding.

[0033] Example 2 This embodiment corresponds to the middle value of the formulation component range, which is a comprehensive performance balanced solution. The total thickness of the composite film is 1.5mm, and the thickness ratio of each layer is 35% for the corrosion-resistant functional layer, 25% for the transition bonding layer, and 40% for the flame-retardant and heat-insulating functional layer.

[0034] Formulas for each layer (by weight parts) Corrosion-resistant functional layer: 75 parts high-density weather-resistant TPO resin, 20 parts compounded sheet barrier filler, 3 parts polyvinylidene fluoride micro powder, 1.2 parts compounded antioxidant, 1.2 parts hindered amine light stabilizer, and 0.6 parts processing aid.

[0035] Transitional adhesive layer: 70 parts maleic anhydride-grafted polyolefin elastomer, 15 parts maleic anhydride-grafted polypropylene, 5 parts nano silica, 0.6 parts silane coupling agent, and 3 parts melamine cyanurate.

[0036] Flame-retardant and heat-insulating functional layer: 60 parts of general-purpose TPO resin, 15 parts of POE elastomer, 20 parts of aerogel-based composite flame retardant, 10 parts of compounded hollow heat-insulating filler, 0.75 parts of silane coupling agent, and 1 part of processing aid.

[0037] Preparation method Except for the process parameters being adjusted as follows, the other operations are the same as in Example 1: ambient temperature mixing time 10 min; temperature of the corrosion-resistant functional layer homogenization section 212℃, temperature of the transition bonding layer homogenization section 202℃, temperature of the flame-retardant and heat-insulating functional layer homogenization section 208℃; temperature of the co-extrusion distributor and die head 210℃; extrusion rate 10 m / min; three roller temperatures of 85℃, 55℃, and 30℃ respectively; corona treatment power 10 kW, aging temperature 45℃.

[0038] Example 3 This embodiment corresponds to the lower limit of the formulation component range, focusing on enhancing mechanical and welding properties. The total thickness of the composite film is 1.2 mm, and the thickness ratio of each layer is 40% for the corrosion-resistant functional layer, 20% for the transition bonding layer, and 40% for the flame-retardant and heat-insulating functional layer.

[0039] Formulas for each layer (by weight parts) Corrosion-resistant functional layer: 85 parts of high-density weather-resistant TPO resin, 10 parts of compounded sheet barrier filler, 1 part of polyvinylidene fluoride micro powder, 0.5 parts of compounded antioxidant, 0.5 parts of hindered amine light stabilizer, and 0.3 parts of processing aid.

[0040] Transitional adhesive layer: 80 parts maleic anhydride-grafted polyolefin elastomer, 10 parts maleic anhydride-grafted polypropylene, 2 parts nano silica, 0.2 parts silane coupling agent, and 1 part melamine cyanurate.

[0041] Flame-retardant and heat-insulating functional layer: 70 parts of general-purpose TPO resin, 10 parts of POE elastomer, 15 parts of aerogel-based composite flame retardant, 5 parts of compounded hollow heat-insulating filler, 0.3 parts of silane coupling agent, and 0.5 parts of processing aid.

[0042] Preparation method Except for the process parameters being adjusted as follows, the other operations are the same as in Example 1: ambient temperature mixing time 8 min; temperature of the corrosion-resistant functional layer homogenization section 205℃, temperature of the transition bonding layer homogenization section 195℃, temperature of the flame-retardant and heat-insulating functional layer homogenization section 200℃; temperature of the co-extrusion distributor and die head 205℃; extrusion rate 15 m / min; three roller temperatures of 80℃, 50℃, and 25℃ respectively; corona treatment power 8kW, aging temperature 40℃.

[0043] Comparative Example 1 This comparative example is a commercially available standard single-layer flame-retardant TPO waterproof membrane, representing the current mainstream technical solution, with a thickness of 1.5mm. The formula is: 70 parts general-purpose TPO resin, 25 parts magnesium hydroxide flame retardant, 3 parts rutile titanium dioxide, and 2 parts antioxidant and processing aids; it is prepared using a single-screw extrusion calendering process.

[0044] Comparative Example 2 This comparative example is a two-layer co-extruded TPO composite film without a transition adhesive layer, used to verify the function of the transition adhesive layer. The total thickness is 1.5 mm, retaining only the corrosion-resistant functional layer and the flame-retardant and heat-insulating functional layer, with the thickness ratios of the two layers being 35% and 65%, respectively; the formulations of the two layers are the same as the corresponding layer formulations in Example 2, and they are prepared using a two-layer co-extrusion casting process, with the remaining process parameters being the same as in Example 2.

[0045] Comparative Example 3 This comparative example is a single-layer blended multifunctional TPO membrane used to verify the effect of the three-layer functional zone design. The total thickness is 1.5 mm. All functional fillers from the corrosion-resistant layer and flame-retardant insulation layer in Example 2 are mixed into the same general-purpose TPO matrix. The formulation is as follows: 65 parts general-purpose TPO resin, 10 parts compounded sheet-like barrier filler, 1.5 parts polyvinylidene fluoride micropowder, 12 parts aerogel-based composite flame retardant, 6 parts compounded hollow insulation filler, 8 parts POE elastomer, 0.5 parts silane coupling agent, 1 part compounded antioxidant, 0.8 parts light stabilizer, and 0.8 parts processing aid. It is prepared using a single-screw extrusion casting process, with the extrusion temperature range the same as the flame-retardant insulation layer parameters in Example 2.

[0046] Comparative Example 4 This comparative example uses a three-layer co-extruded composite film with a traditional flame-retardant system to verify the synergistic effect of the aerogel-based composite flame retardant. The overall structure, layer thickness ratio, and process parameters are the same as in Example 2, except that the aerogel-based composite flame retardant in the flame-retardant and heat-insulating functional layer is replaced with an equal mass of magnesium hydroxide flame retardant.

[0047] Comparative Example 5 This comparative example is a three-layer co-extruded composite film using a single grafted resin transition layer, used to verify the polar gradient design effect of the dual-grafted compound system. The overall structure, layer thickness ratio, and formulations of the corrosion-resistant layer and flame-retardant heat insulation layer are the same as in Example 2, the only difference being that: the transition bonding layer uses 75 parts of a single maleic anhydride-grafted polyolefin elastomer, without adding maleic anhydride-grafted polypropylene, and the amounts of other additives remain unchanged; the preparation process is the same as in Example 2.

[0048] Comparative Example 6 This comparative example is a three-layer co-extruded composite film with a basic transition layer, used to verify the functional contributions of nano-silica and synergistic flame retardants in the transition layer. The overall structure, layer thickness ratio, and formulations of the corrosion-resistant layer and flame-retardant heat insulation layer are the same as in Example 2, except that: the transition bonding layer does not contain nano-silica and melamine cyanurate, but is composed of 70 parts of maleic anhydride-grafted polyolefin elastomer, 15 parts of maleic anhydride-grafted polypropylene, and 0.6 parts of silane coupling agent; the preparation process is the same as in Example 2.

[0049] Comparative Example 7 This comparative example is a three-layer co-extruded composite film using a single insulating filler, used to verify the synergistic insulating effect of the double hollow microsphere composite. The overall structure, layer thickness ratio, and matrix formulation of each layer are the same as in Example 2, the only difference being that: a single hollow glass microsphere is used instead of the composite hollow insulating filler in the flame-retardant and heat-insulating functional layer, the total mass of the filler is the same as in Example 2, and the amount of aerogel-based composite flame retardant remains unchanged; the preparation process is the same as in Example 2.

[0050] Comparative Example 8 This comparative example is a three-layer co-extruded composite film with physically mixed fillers, used to verify the synergistic effect of the load-bearing structure compared to physical mixing. The overall structure, layer thickness ratio, and matrix formulation of each layer are the same as in Example 2, except that in the flame-retardant and heat-insulating functional layer, ammonium silica aerogel, ammonium polyphosphate, aluminum diethyl phosphite, and hollow heat-insulating filler are physically mixed and added, with the mass ratio of each component being the same as in Example 2, and the total filler mass being equal; the preparation process is the same as in Example 2.

[0051] Comparative Example 9 This comparative example is a three-layer co-extruded composite film without fluorinated polymer micropowder, used to verify the synergistic effect of PVDF micropowder and sheet-like barrier filler on corrosion resistance. The overall structure, layer thickness ratio, and formulations of the transition layer and flame-retardant heat insulation layer are the same as in Example 2, the only difference being that: the corrosion-resistant functional layer does not contain polyvinylidene fluoride micropowder, and the reduced amount is made up by high-density weather-resistant TPO resin; the preparation process is the same as in Example 2.

[0052] Comparative Example 10 This comparative example is a three-layer co-extruded composite membrane using a single corrosion-resistant filler, used to verify the synergistic barrier effect of the compounded sheet-like barrier filler. The overall structure, layer thickness ratio, and formulations of the transition layer and flame-retardant heat insulation layer are the same as in Example 2, the only difference being that: a single ultrafine talc powder is used instead of the compounded sheet-like barrier filler in the corrosion-resistant functional layer, and the total mass of the filler is the same as in Example 2; the preparation process is the same as in Example 2.

[0053] Comparative Example 11 This comparative example is a three-layer co-extruded composite film exceeding the parameter range, used to verify the critical rationality of the formulation and thickness parameter range of the present invention. The total thickness is 1.0 mm, and the thickness proportions of each layer are as follows: corrosion-resistant functional layer 25%, transition bonding layer 15%, and flame-retardant and heat-insulating functional layer 60%. In the flame-retardant and heat-insulating functional layer, the amount of aerogel-based composite flame retardant is 35 parts, the amount of compounded hollow heat-insulating filler is 18 parts, and the proportions of the remaining components are the same as in Example 2. The preparation process adjusts the roller speed according to the thickness, and the remaining parameters are the same as in Example 2.

[0054] Performance testing The performance of the above-described embodiments and comparative samples was tested according to the corresponding national standards, and the test results are shown in the table below: Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-4

[0055] Table 2 Performance test results of Comparative Example 5-11

[0056] Results Analysis The test results show that: The composite membranes prepared in Examples 1-3 of this invention possess excellent corrosion resistance, flame retardancy, and heat insulation properties, while maintaining good mechanical and weldability properties, with balanced and synergistic performance across all aspects. By adjusting the proportion of formulation components and layer thickness, different performance emphases can be achieved to meet the needs of different application scenarios such as chemical corrosion protection, building roofing, and power battery protection.

[0057] Compared with Comparative Example 1, the composite membrane of the present invention has significantly improved acid and alkali corrosion resistance, flame retardancy and heat insulation effect, solving the defects of traditional single-layer TPO materials with single function and insufficient comprehensive performance.

[0058] Compared with Comparative Example 2, the present invention significantly improves the initial peel strength and peel strength retention rate after thermal aging by introducing a polar grafted polyolefin transition adhesive layer, effectively avoiding the failure problems of easy delamination and bubbling in multilayer co-extruded structures, and ensuring the structural stability for long-term use.

[0059] Compared with Comparative Example 3, the present invention adopts a three-layer functional partition design, which avoids the performance antagonism and interface defects of multiple functional fillers in the same matrix. The mechanical properties, corrosion resistance and weldability are all better, and the technical bottleneck of single-layer blending modification is difficult to achieve multiple functions.

[0060] Compared with Comparative Example 4, the aerogel-based composite flame retardant and hollow heat insulation filler compound system used in this invention achieves a better synergistic effect of flame retardancy and heat insulation under the same filling amount, while retaining the flexibility and processing performance of the material, demonstrating the technical advantages of filler compounding and synergistic effect.

[0061] Compared to Example 2, Comparative Example 5, which used a single grafted resin as a transition layer, showed a decrease in initial interlayer peel strength of approximately 28.6%, a decrease in peel strength retention rate after heat aging from 85.7% to 66.7%, and a decrease in strength retention rate after acid and alkali immersion of approximately 6 percentage points. This indicates that relying solely on the bonding effect of a single grafted resin cannot simultaneously meet the interfacial bonding requirements of the upper low-polarity weather-resistant TPO and the lower high-filler polarity system. This solution, by compounding two polyolefins with different grafting rates to form a polarity gradient, is not a simple mixing of conventional adhesive materials, but rather a targeted solution to the interlayer polarity differences caused by the three-layer functional partitioning.

[0062] In Comparative Example 6, after removing nano-silica and melamine cyanurate from the transition layer, the peel strength retention rate after thermal aging further decreased, and the oxygen index also showed a significant decline. This indicates that nano-silica is not a common reinforcing filler, but rather forms an additive migration barrier network in the transition layer, inhibiting the migration of flame retardants and fluorinated additives to the interface; MCA is also not an optional flame retardant additive, but rather forms an interlayer mechanical flame retardant effect with the underlying phosphorus-nitrogen flame retardant system. Together with the double-grafted resin matrix, the transition layer simultaneously undertakes four functions: interfacial bonding, migration inhibition, synergistic flame retardancy, and stress buffering. This exceeds the conventional understanding in the field that the transition layer only serves an adhesive function.

[0063] Compared to Example 2, Comparative Example 7, which used a single hollow glass microsphere as the insulating filler, showed an increase in thermal conductivity of approximately 11.8%, with a significant decrease in the insulating effect. This indicates that the 1:1 blend of hollow glass microspheres and ceramic microspheres is not an arbitrary combination of the two fillers, but rather an optimization of the packing structure through particles of different sizes and strengths, reducing solid-phase contact hotspots. Simultaneously, the high-temperature stability of the ceramic microspheres provides an inorganic framework for the carbon layer, achieving simultaneous optimization of both insulating performance and high-temperature structural stability. The optimal overall performance under this ratio cannot be linearly derived from the known effects of a single filler.

[0064] Comparative Example 8 changed the aerogel, flame retardant, and hollow filler to a physical mixture. Under the premise that the total filler mass was completely consistent, the oxygen index decreased by 2.8 units, the thermal conductivity increased by about 16.2%, and the elongation at break decreased by about 17.3%. This proves that the aerogel-supported flame retardant and hollow filler in this solution are not simply physically compounded, but rather the flame retardant dispersibility is improved through a chemically bonded loading structure, the porous structure of the aerogel is used to catalyze char formation, and the rigid framework of the hollow microspheres supports the char layer. The three form a complete synergistic link of "dispersion-char formation-support". The simultaneous improvement of flame retardancy, heat insulation, and mechanical properties is an unexpected technical effect.

[0065] Compared to Example 2, in Comparative Example 9, the tensile strength retention rate after acid and alkali immersion decreased by approximately 5 to 7 percentage points after removing the polyvinylidene fluoride (PVDF) micropowder from the corrosion-resistant layer. This indicates that the PVDF micropowder is not a common weather-resistant additive, but rather works synergistically with the sheet-like barrier filler: the sheet-like filler constructs a tortuous penetration path, while the PVDF micropowder fills the gaps between the sheets and forms a low surface energy barrier. Together, they constitute a multi-level corrosion-resistant system of "path barrier + surface energy shielding," which offers superior corrosion resistance compared to a single filler barrier.

[0066] In Comparative Example 10, replacing the compounded sheet-like barrier filler with a single ultrafine talc powder further reduced the corrosion resistance. This indicates that the 2:1:1 compound of talc powder, mica powder, and organically modified montmorillonite forms a denser "brick-wall" barrier network through the synergistic stacking of fillers with different aspect ratios and sheet sizes. Its permeation path extension effect is significantly better than that of a single filler, and it is not a simple combination of conventional fillers in this field.

[0067] Compared to Example 2, Comparative Example 11, after reducing the total thickness and increasing the amount of flame-retardant and heat-insulating filler, showed a slight increase in the oxygen index, but the material's elongation at break, interlayer peel strength, corrosion resistance, and hot-air welding performance all deteriorated significantly, and the processing stability also decreased markedly. This indicates that the thickness range, layer thickness ratio, and filler dosage range defined by this invention are not arbitrary parameters that can be obtained through conventional process optimization, but rather a critical and reasonable range obtained by comprehensively balancing corrosion resistance, flame retardancy, heat insulation, mechanical properties, weldability, and processability, thus possessing the inventiveness of the invention.

[0068] In summary, this invention does not simply juxtapose known technologies such as "three-layer functional partitioning, grafted polyolefin transition layer, aerogel flame retardancy, hollow microsphere thermal insulation, and sheet-like filler corrosion resistance." Instead, it forms a mutually supportive overall technical solution through the directional separation of the functions of each layer, the multifunctional interface design of the transition layer, the load-bearing composite structure of the filler, and the precise matching of parameter ranges. This solution simultaneously improves the three core performance characteristics while effectively maintaining the mechanical properties and weldability of the material.

Claims

1. A multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film, characterized in that, It is a three-layer co-extruded integral molding structure, consisting of a corrosion-resistant functional layer, a transition bonding layer, and a flame-retardant and heat-insulating functional layer from top to bottom, with the sum of the thicknesses of the three layers being 100%. The corrosion-resistant functional layer uses high-density weather-resistant TPO resin as the matrix, and adds compounded sheet-like barrier filler and polyvinylidene fluoride micro powder; the compounded sheet-like barrier filler is a mixture of ultrafine talc powder, mica powder and organic modified montmorillonite in a mass ratio of 2:1:

1. The transitional adhesive layer uses maleic anhydride-grafted polyolefin elastomer and maleic anhydride-grafted polypropylene as the matrix, with the addition of nano-silica and melamine cyanurate; the grafting rate of the maleic anhydride-grafted polyolefin elastomer is 0.8% to 1.2%, and the grafting rate of the maleic anhydride-grafted polypropylene is 1.0% to 1.5%; The flame-retardant and heat-insulating functional layer uses general-purpose TPO resin and POE elastomer as the matrix, and adds aerogel-based composite flame retardant and compound hollow heat-insulating filler; the aerogel-based composite flame retardant is a composite of ammonium polyphosphate and diethylaluminum hypophosphite supported on ammonium silica aerogel, with a loading mass ratio of aerogel:ammonium polyphosphate:diethylaluminum hypophosphite = 1:3:2; the compound hollow heat-insulating filler is a mixture of hollow glass microspheres and hollow ceramic microspheres with a mass ratio of 1:

1.

2. The multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film according to claim 1, characterized in that, The total thickness of the composite membrane is 1.2 to 2.0 mm, of which the corrosion-resistant functional layer accounts for 30% to 40%, the transition bonding layer accounts for 20% to 30%, and the flame-retardant and heat-insulating functional layer accounts for 30% to 40%.

3. The multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film according to claim 1, characterized in that, The corrosion-resistant functional layer, by weight, comprises the following components: 65 to 85 parts of high-density weather-resistant TPO resin, 10 to 30 parts of compounded sheet-like barrier filler, 1 to 5 parts of polyvinylidene fluoride micro powder, 0.5 to 2 parts of compounded antioxidant, 0.5 to 2 parts of hindered amine light stabilizer, and 0.3 to 1 part of processing aid. The polyvinylidene fluoride micropowder has a particle size of 5 to 10 μm, the compound antioxidant is a compound system of hindered phenols and phosphites, and the processing aid is polyethylene wax or calcium stearate.

4. The multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film according to claim 1, characterized in that, The transition adhesive layer, by weight, comprises the following components: 60 to 80 parts of maleic anhydride-grafted polyolefin elastomer, 10 to 20 parts of maleic anhydride-grafted polypropylene, 2 to 8 parts of nano-silica, 0.2 to 1 part of silane coupling agent, and 1 to 5 parts of melamine cyanurate. The silane coupling agent is KH-550.

5. The multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film according to claim 1, characterized in that, The flame-retardant and heat-insulating functional layer, by weight, comprises the following components: 50 to 70 parts of general-purpose TPO resin, 10 to 20 parts of POE elastomer, 15 to 30 parts of aerogel-based composite flame retardant, 5 to 15 parts of compounded hollow heat-insulating filler, 0.3 to 1.2 parts of silane coupling agent, and 0.5 to 1.5 parts of processing aid.

6. A method for preparing the multifunctional corrosion-resistant, flame-retardant, and heat-insulating TPO co-extruded composite film according to any one of claims 1 to 5, characterized in that, The process involves a three-layer co-extrusion casting process, specifically including the following steps: (1) Preparation of aerogel-based composite flame retardant and preparation of functional masterbatch: First, the silica aerogel is aminated by silane coupling agent, and then ammonium polyphosphate and aluminum diethylphosphite are loaded by impregnation loading method. After drying, the aerogel-based composite flame retardant is obtained; the composite flame retardant and the compound hollow heat insulation filler are prepared into functional masterbatch. (2) Ingredients and mixing: According to the formula ratio of each layer, the matrix resin, functional masterbatch and remaining additives are put into the high-speed mixer and mixed evenly at room temperature, and then fed into the corresponding extruder hoppers respectively. (3) Three-layer co-extrusion molding: Three single-screw extruders are used to plasticize three layers of material respectively. The melt is stacked by the co-extrusion distributor and then extruded into a preform through a flat die. (4) Casting, cooling and shaping: The extruded composite film preform is introduced into a three-roll casting calender and is shaped by segmented gradient cooling; (5) Post-processing and winding: After cooling and shaping, the composite film is subjected to surface corona treatment and constant temperature aging to eliminate internal stress. Finally, it is cut to length, inspected and wound to obtain the finished product.

7. The preparation method according to claim 6, characterized in that, The temperature parameters of each extruder in step (3) are set as follows: Corrosion-resistant functional layer extruder: feeding section 180 to 190°C, plasticizing section 200 to 210°C, homogenizing section 205 to 220°C; Transitional adhesive layer extruder: feeding section 170 to 180°C, plasticizing section 190 to 200°C, homogenizing section 195 to 210°C; Flame-retardant and heat-insulating functional layer extruder: feeding section 175 to 185°C, plasticizing section 195 to 205°C, homogenizing section 200 to 215°C; The temperature of the co-extrusion distributor and die head is 205 to 215°C; the overall melt extrusion rate is 8 to 15 m / min.

8. The preparation method according to claim 6, characterized in that, In step (4), the temperature parameters of the three-roll casting calender are set as follows: the temperature of the first roll is 80 to 90°C, the temperature of the second roll is 50 to 60°C, and the temperature of the third roll is 25 to 35°C.

9. The preparation method according to claim 6, characterized in that, In step (5), the corona treatment power is 8 to 12 kW, the constant temperature aging temperature is 40 to 50 ℃, and the aging time is 24 h.